Transfer Pricing, Agency Costs, and Financial Reporting Aggressiveness: An Empirical Study in Indonesia - Eva Herianti; Amor Marundha (Universitas Muhammadiyah Yogyakarta, Indonesia, 2019)
The purpose of this study is to explore the effect of transfer pricing strategy and agency cost on financial reporting aggressiveness. This paper used 61 manufacturing industries listed on the Indonesia Stock Exchange from 2013 to 2017 period among which 305 companies were selected by purposive sampling method to be studied. The research questions were tested using panel data regression analysis. This study found that transfer pricing strategy had no significant effect on financial reporting aggressiveness but agency cost had negative and significant effect on financial reporting aggressiveness. Furthermore, control variables as growth and return on asset had positive and significant effect on financial reporting aggressiveness while size had negative and significant effect on financial reporting aggressiveness. Results of this study indicated that managers did not use transfer pricing strategy in managing earnings because there was regulation of OECD to control manager behaviour in implementing transfer pricing strategy. In addition, agency cost was one of the important factors in reducing manager behaviour to meet their interests.